O outro sob o olhar da criança: representação e linguagem - Alessio, Priscila Chuarts (2018)
This study is an interdisciplinary research in the areas of Language and Sociology whose purpose is to verify how the representations about the other are verified in two distinct groups of children of the same age (six to eleven years old): one group of children from a nongovernmental organization that serves children in need and another group composed of children from a private school system. These two groups may or may not have different representations about the other, comparing them we can identify how the social relations of each group are constructed, making us observe how the social organizations of local society are arranged. It is intended to answer some questions: Who is this other and what is the relationship of this other with each group? Does the socioeconomic situation prevail in the construction of representations about the other? Because they are children belonging to the same region, but located in different socioeconomic poles, what is the relationship that can be made between the different representations if they are considered resonances of representations that children learn from their cultural context? Our main objective is to find out what the representations of each group are, and, to identify how they are organized in the social relations of each group with their specific other. The specific objectives are to verify how these representations are constructed considering the social context in which the children are inserted and to analyze the relation of the representations of one group with those of the other group. For data generation, a course was held in both institutions in a total of 8h / a each, addressing the following topics: Indian, Black, Haitian and social inequality. Classes were recorded and later transcribed for better data analysis. As a research methodology, this work deals with action-research, considering the interaction of the researcher with the groups, as well as the interventions made by all the subjects involved in the contexts researched. Theoretical basis was used by theorists from the so-called Cultural Studies, as well as authors who consider the multiplicity of language. As a result of the research, it is possible to say that children are surrounded by diverse forces coming from their socio-cultural environments that perpetuate prejudiced discourses and that, although they can identify with others, they do not do so because there are no positive consequences in admitting the identity of other.